2018
DOI: 10.3989/gya.0667171
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pecan nut expeller cake and effect of storage on its microbiological and oxidative quality

Abstract: SUMMARY:Pecan nut expeller cake (PNEC), a by-product of pecan oil extraction, was characterized and the effect of packaging and storage conditions was investigated. Samples were packaged under vacuum or in normal atmosphere and stored (10 or 20 ºC) for 12 months. Its composition, water and oil absorption, fatty acids profile, lipid oxidation (thiobarbituric acid reactive substances, TBARS), antioxidant activity [Diphenyl-1-(2,4,6-trinitrophenyl)hydrazyl] radical, DPPH• and [(2,2′-azinobis-(3-ethylbenzothiazoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
13
1
2
Order By: Relevance
“…It was concluded that this method of preservation was efficient and it is preferable the use of paper because is more eco-friendly [26]. It was demonstrated that peanut oilcake, stored twelve months in vacuum packaging with low permeability, regardless of the temperature retained its quality (good water/oil absorption and high content of unsaturated fatty acids), antioxidant capacity, and low microorganism yeast (due to the oxygen restriction that delays their growth and lipid oxidation) [27].…”
Section: Oilseed Production Process and By-products Physiochemical Propertiesmentioning
confidence: 99%
“…It was concluded that this method of preservation was efficient and it is preferable the use of paper because is more eco-friendly [26]. It was demonstrated that peanut oilcake, stored twelve months in vacuum packaging with low permeability, regardless of the temperature retained its quality (good water/oil absorption and high content of unsaturated fatty acids), antioxidant capacity, and low microorganism yeast (due to the oxygen restriction that delays their growth and lipid oxidation) [27].…”
Section: Oilseed Production Process and By-products Physiochemical Propertiesmentioning
confidence: 99%
“…They contain many phyto‐chemical substances that may contribute to their overall antioxidant activity (Pinheiro do Prado, ). When pecan nut cake is stored under oxygen restriction lipid oxidation is inhibited with consequent protection of fatty acids and antioxidants present in this product (Marchetti, Romero, Andrés, & Califano, ). Pecan nuts are also a dietary source of alpha‐tocopherol (12.2 ± 3.2 mg/g), gamma‐tocopherol (168.5 ± 15.9 mg/g), and squalene (151.7 ± 10.8 mg/g) (Ryan, Galvin, O'Connor, Maguire, & O'Brien, ).…”
Section: Resultsmentioning
confidence: 99%
“…En productos cárnicos emulsionados, las proteínas de soya promueven la absorción y retención de grasa, por tanto se disminuyen las pérdidas durante la cocción y se mantiene la estabilidad dimensional. El IAL de la harina de L. culinaris fue de 2,01 ml de aceite/g de muestra; menor a lo reportado para la harina de Glycine max (3,17 ml de aceite/g de muestra), pero mayor a la harina de Vigna Sinensis (1,73 ml de aceite/g de muestra), Triticum durum (0,38 ml de aceite/g de muestra) y Phaselous vulgaris (1,36 ml de aceite/g de muestra) y muy similar a la harina de Erthrina edulis (2,54 ml de aceite/g de muestra), lo cual es un indicador de que puede ser empleada en productos cárnicos, porque promueve la absorción y retención de grasa, lo que en consecuencia, podría ayudar a disminuir las pérdidas durante el escaldado y a mantener la estabilidad de la emulsión (Marchetti, Andrés y Califano, 2014). La habilidad para absorber y retener dichos compuestos es un indicativo de la capacidad que tienen las proteínas para enlazar agua, que influye drásticamente en la textura y las propiedades sensoriales de los productos a consumir (Goesaert et al, 2005).…”
Section: Resultsunclassified
“…Los extensores cárnicos tienen propiedades funcionales como la retención de agua, la emulsificación de las grasas, absorción de lípidos y la gelificación (Olmedilla-Alonso, Jiménez-Colmenero y Sánchez-Muniz, 2013). Así la presencia de uno u otro extensor no solo ayuda en la parte económica a la fórmula, sino que además concede rendimiento al proceso y al producto como tal (Arief et al, 2014;Marchetti, Andrés y Califano, 2014).…”
Section: Introductionunclassified